Stakeholders of multinational companies: the case of Korean multinational companies in Brazil - Kim, JeongHeon (2015)
The objective of this study is to investigate the difference between stakeholders\' characteristics in Brazil and in Korea which are perceived by managers of Korean MNCs (This study has been conducted based on data collected from South Korean companies so whenever \"Korea\" and \"Korean\" are mentioned, they should be interpreted as relating to South Korea.) In international business, the multinational environment has become challenging to MNCs, which stem from the multidimensional environments of the countries, such as macroeconomic, cultural, political and legal environments, among others. That is, managing stakeholders in a different environment has become influential to managerial performance of MNCs as well. Thus, in order to identify the main stakeholders and issues related to them as management strategic focus, the stakeholder\'s characteristics of Brazil and Korea were compared and empirically approached. The data collection was done through in-depth interviews with the Korean managers of several Korean multinational companies operating in Brazil, who belong to the department that deals with local stakeholders either directly or indirectly in the host country. According to the data analysis, among the ten categories of stakeholders identified by Clarkson, the Korean companies are mainly interacting with eight stakeholders: employee, financial institution, customer, supplier, government, trade association, labor union and media, and there is effectively not only no interaction with the other two categories of NGO and community in Brazil but also no difference in their characteristics between Korea and Brazil. In reference to the distinct characteristics of the local stakeholders compared to the stakeholders in Korea, five characteristics were identified with employees, three with governments, three with financial institutions, two with customers, two with suppliers and one with trade associations, but no difference was identified with media. Managers perceived that all kinds of stakeholders are more unmanageable in Brazil than in Korea, excepting the customers. It was shown that there is a bigger difference of that manageability with employees, suppliers, financial institutions and trade associations and less difference with governments, labor unions and media, in this particular order. Analyzing the difference of the stakeholder\'s influence between the two countries, it was established that there is no difference in customers, labor unions and trade associations, there is a little difference in financial institutions and suppliers, and a bigger difference in governments and media. It is a difficult situation to find not only the study that compares the characteristics of the stakeholders but also the comparative study that deals with specific countries\' cases. The result of this comparison among the characteristics can help managers grasp the causes and existing strategies analyzed for the problems, as well as effectively establish strategies to manage the stakeholders. However, because of the limitations of the study, which collected data from only a few industries, in future research there will be a need to conduct a comprehensive study with data collected from all kinds of industries. Then, it will be possible to generalize stakeholders\' characteristics. In addition, quantitative studies need to be done in relation to the characteristics presented as a result after this analysis process so that the researchers will be able to verify the influences of stakeholders on the multinational companies statistically. clientes, sindicatos e associações de classe; pouca diferença foi identificada em relação às instituições financeiras e fornecedores e grande diferença em governos e mídia. É difícil encontrar um estudo que não apenas compare as características dos stakeholders, mas também compare as especificidades dos países. Os resultados desta comparação entre características pode auxiliar os gestores a compreender as causas e estratégias existentes para os problemas, assim como efetivamente estabelecer estratégias para gestão de stakeholders. Todavia, considerando as limitações deste estudo, que coletou dados de poucas indústrias, nas pesquisas futuras haverá a necessidade de conduzir um estudo mais abrangente, coletando dados de todos os tipos de indústria. Dessa forma, será possível generalizar as características dos stakeholders. Além disso, necessita-se realizar estudos quantitativos em relação às características apresentadas como um resultado posterior a este processo de análise e então os pesquisadores poderão verificar estatisticamente as influências dos stakeholders nas empresas multinacionais.